Intervista a Marcello Ravveduto: Mafia e storiografia. Premesse culturali e prospettive attuali - Marcello RAVVEDUTO (Diacronie. Studi di Storia Contemporanea, 2019)
The historian Marcello Ravveduto, in the interview given to Diacronie. Studi di Storia contemporanea on 10 October 2019, presents his assessments on the mafia phenomenon by building, on the one hand a detailed historical phenomenology of the “mafia realities” and the modus operandi of organized crime in our country and, on the other hand, outlining new research perspectives in the field of mafia studies.